Association between lipid accumulation product and the risk of colon cancer in adults: A population-based study. - Renjie Guo; Weiming Wei (PLoS ONE)
Background The purpose of this study was to look into any potential connections between the occurrence of colon cancer and the condition of the body of lipid accumulation product (LAP) index. Methods Using data from the 2009-2018 National Health and Nutrition Examination Survey (NHANES), we performed a cross-sectional analysis with 24,592 individuals. Utilizing multivariate logistic regression modelling, the relationship between LAP levels and colon cancer risk was investigated. Subgroup analysis, trend test, interaction test, and stratified smoothed curve were also carried out. Results LAP levels and colon cancer risk were positively correlated after controlling for potential covariates (OR = 10.56, 95% CI: 2.40-46.53), the findings of trend tests are statistically significant. In particular groups, subgroup analysis revealed a positive connection between LAP levels and the risk of colon cancer. The association between LAP levels and colon cancer risk was shown to be M-shaped in the group under 60 years old, inverted V-shaped in the female and no-diabetes groups, and inverted L-shaped in the smoking and no-hypertensive groups, according to stratified smoothed curve fitting. Conclusions According to our findings, there is a strong correlation between LAP levels and the risk of colon cancer.